Topics, Sources and Applicability of Coaching Knowledge in Police Training - Staller, Mario S.; Koerner, Swen; Abraham, Andrew; Poolton, Jamie M. (Frontiers in Education, 2022)
The current study explored police trainers’ perceptions of their actual and preferred methods of acquiring new coaching knowledge; the types of knowledge they currently require and/or desire; and how they apply new knowledge. A total of 163 police trainers from Germany and Austria participated in the study. The responses were analysed using an inductive approach. The results showed that police trainers thought they needed knowledge of pedagogy, policing, and self-development, with reasons being centred around a need to optimise learning, training content and the engagement of learners within the training sessions. Preferred methods of learning focused predominantly around informal and non-formal opportunities, the reasons for which were social interaction, the reality-based focus of the content and the perceived quality. Finally, police trainers identified technical or tactical policing knowledge, or knowledge specific to the delivery of police training as useful, recently acquired coaching knowledge, mainly because it was perceived to have direct application to their working practices. Based on these findings, it is suggested police trainers are in need of context-specific knowledge and support to develop the declarative knowledge structures that afford critical reflection of new information.